2. Work in Progress: PhD thesis: Βοιωτικοὶ Κοῦροι: An Ancient “Heritage Community”? New Analyses for a Regional Sculptural Production - Mastropietro, Lucrezia, (Teiresias Journal Online, 2025)
Lucrezia MASTROPIETRO (Scuola Superiore Meridionale) PhD thesis: Βοιωτικοὶ Κοῦροι: An Ancient “Heritage Community”? New Analyses for a Regional Sculptural Production